Analysis of the Effectiveness of the Assessment Center as A Competency Testing Method for Police Sector Chiefs (KAPOLSEK) in Improving Police Performance within the Metro Jaya Regional Police - Afriska Nababan; Vita Mayastinasari; Joko Setiono (Jurnal Greenation Sosial dan Politik, 2025)
The position of Sector Police Chief (Kapolsek) holds a strategic role within the operational structure of the Indonesian National Police (Polri), especially in maintaining security and public order at the sub-district level. To ensure professionalism and accountability of Kapolsek officials, a selection method is needed that can objectively measure competence. The Assessment Center emerges as a competency-based mechanism considered to have high validity in assessing managerial, technical, and socio-cultural dimensions. This study analyzes the effectiveness of the Assessment Center in competency testing for the Kapolsek position within the Metro Jaya Regional Police, using a normative juridical approach and descriptive analysis. The legal foundations used include Law Number 2 of 2002 concerning the Indonesian National Police, Government Regulation Number 11 of 2017 in conjunction with Government Regulation Number 17 of 2020 concerning Civil Servant Management, as well as the Regulation of the Indonesian National Police Number 12 of 2024 concerning the Assessment Center within the Police environment. The results of the study show that the Assessment Center is a method that is normatively and technically in line with the principles of meritocracy and good human resource governance. However, its implementation still faces challenges such as a lack of assessors, infrastructure limitations, and organizational culture resistance to a competency-based selection system. Institutional strengthening and consistent enforcement of the merit system are required so that the results of the Assessment Center truly serve as an objective basis for the appointment of Kapolsek positions. With the optimization of this system, the National Police is expected to form sectoral leadership that is professional, adaptive, and oriented toward public service.